The prospects for fictionalist inquiry in psychology. (December 2017) - Smythe, William E.
Abstract: This paper undertakes a critical appraisal of the prospects for fictionalist inquiry in psychology, which runs contrary to the traditional dissociation between fiction and knowledge-laden discourse. Following a review of the contested boundary between fiction and nonfiction, a portrait of essential aspects of fiction emerges, which includes authorial warrant, imaginative prescription, and performative engagement . The paper then proceeds to outline fictionalism as a philosophical approach, with reference to early and more modern variants of the position. This leads to a little discussed epistemic position called the fictional stance, which is then developed and applied to various psychological domains including the psychology of fiction, the fictional constructions of psychology, and the narrative study of lives. The viewpoint that emerges sees the epistemic value of fictional thinking in the unique access it provides to intuitive powers of the psychological imagination and to non-conceptual understandings of psychological life.